The SOREM-Led Induction Method (SLIM): A Novel and Theoretically Grounded Approach to Eliciting Out-Of-Body Experiences - Hollier, Peter (Journal of Scientific Exploration, 2023)
In parapsychological literature, out-of-body experiences (OBEs) appear closely correlated to the phenomenon of sleep paralysis (SP), with some authors referring to the SP state as a “gate” or “launching pad” for OBEs. Given the notorious difficulty of eliciting OBEs voluntarily using conventional methods, this paper proposes a novel methodology for eliciting OBEs, involving the induction of SP as a precursor condition. The relationship between sleep onset rapid eye movement (SOREM) sleep, SP, and OBEs are discussed, as is the work of earlier researchers who first elicited SOREM and sleep paralysis in the sleep laboratory. The results of preliminary testing of this methodology are briefly described.